Impact of Video-Based Health Education on Adolescents' Awareness of Frambusia at Puskesmas Tairi - Prima Dewi Kusumawati; Reni Nurhidayah; La Joni (Universitas STRADA Indonesia, 2024)
Background: Frambusia, a neglected tropical disease, poses a significant health challenge in tropical regions, including Indonesia. The disease predominantly affects children and adolescents, especially in areas with poor sanitation. This study evaluates the impact of video-based health education on adolescents' knowledge of Frambusia at Puskesmas Tairi. Purpose: To assess the effectiveness of video-based education in enhancing adolescents' awareness and understanding of Frambusia disease. Method: A pre-experimental design with a one-group pretest-posttest approach was used. A sample of 85 adolescents, aged 12 to 15 years, received health education on Frambusia through video media. Knowledge levels were assessed using pretest and posttest questionnaires, analyzed with the Wilcoxon signed-rank test. Results: Before the intervention, 85.7% of respondents had poor knowledge about Frambusia. Post-intervention, 94.3% of respondents demonstrated good knowledge. The Wilcoxon signed-rank test revealed a significant improvement in knowledge (p < 0.001). Discussion: The use of video-based education significantly enhanced adolescents' understanding of Frambusia. This approach effectively engages both auditory and visual senses, leading to better knowledge retention and potential community impact. Conclusion: Video-based health education is a powerful tool for improving disease awareness among adolescents. Implementing similar methods could benefit other regions with high incidence of Frambusia and other neglected diseases.